A study on the factors influencing organizational commitment in Kolej Poly-Tech Mara Sdn Bhd / Azzah Izzati Abu Bakar - Abu Bakar, Azzah Izzati (Faculty of Business and Management, 2013)
Purpose: The purpose of this study was to assess the relationship between personality and perceived organization supports towards organizational commitment. Method: One hundred staff in 2 divisions which are administration and academic (lecturer) at Kolej Poly-Tech Mara was sent questionnaires to complete. The survey is about factor that influencing the organizational commitment in KPTM such as personality and perceived organization support. Results: 74 respondents completed the questionnaires. The result revealed that there is positive and strong relationship between personality and organizational commitment meanwhile perceived organizational support also has relationship with organizational commitment but it’s just moderate relationship. Conclusion: The personality and perceived organization support towards organizational commitment has a relationship and personality is more influence factors towards organizational commitment. Job performance might be increase if individuals put a high commitment on their task.